Environmental Pollution Prevention Effort Soun Noodle Industry Waste in Two (2) Village, Tulung District, Klaten Regency - Imam Wisnu Kurniyanto; Ipmawan Muhammad Iqbal; Farhan Rizky Darmawan; Muhammad Faizal Rifai; Nugroho Budi Kisdiyanto (Proceeding International Conference Restructuring and Transforming Law, 2022)
Pucang Miliran Village and Daleman Village are the largest buckwheat noodle industry/SME centers in Tulung District, Klaten Regency, Central Java.Pollution is not only caused by large and medium scale industries, but can also be caused by small scale industries, one of which is the vermicelli noodle industry which also produces liquid waste and solid waste. The problems in this study are how to prevent environmental pollution due to the production of home-based "soun noodles" in Tulung District, Klaten Regency, and what are the obstacles experienced in the process of preventing environmental pollution caused by the production of home- based "soun noodles" industries in 2 villages, namely Pucang Miliran Village and Daleman Village, Tulung District, Klaten Regency.This research is an empirical legal research, data obtained through interviews with informants. Liquid waste originating from the chlorine disposal process and solid waste in the form of starch fiber is discharged into the river, causing river water pollution. In this case, BLH is not optimal in handling this problem due to lack of supervision and budget. Most of the small-scale vermicelli noodle industry, are not required to have a TDI, so they are free from supervision.In addition, the impact of industrial activities on environmental pollution has not been maximized, due to limited funds and the number of BLH officers. Based on these results, it is recommended to the Investment Office and Licensing Unit and BLH to continue to monitor and provide counseling to business activity actors and BLH to encourage business actors to conduct joint IPAL together.